The Use of Web 2.0 Tools and Technologies in English Language Teaching-Learning Process - Roy , Piu (Gyan Management Journal, 2023)
English language instruction increasingly makes use of web 2.0 tools  and technologies as the most cutting-edge example of internet-based  technology. Wikis, blogs, podcasts, social networks, and video conferencing  are some of the most common examples of Web 2.0 technologies that have  shown their use in language instruction and study. In the last ten years, Web  2.0 has become an essential part of the educational process, both within  and outside the traditional classroom setting. Almost all language classes  have used various technological tools and resources in recent years. Using  multiple technologies has facilitated and improved students’ ability to learn  new languages. The use of technology enables teachers to adapt classroom  activities, which ultimately speeds up the language acquisition process. It is  becoming more critical for teachers to use the tools and technology offered  by Web 2.0 to encourage language learning in their classes. This research  investigates the impact that contemporary technology has on the process  of learning English as a second or foreign language. We looked at various  mindsets to see what technology motivates English language learners to  enhance their learning abilities. The researcher defines technology and  explains how technology may be integrated into educational settings,  namely language courses. It reviews previous studies on using Web 2.0  tools and technologies to enhance language learning abilities and makes  recommendations for the improved use of these technologies, which  aid students in improving their learning abilities. In addition, it reviews  previous studies on using Web 2.0 tools and technologies to enhance  language learning abilities. The anticipated results from the previously  published research demonstrate that students’ language-learning abilities  improve when they effectively use emerging technologies.
Keywords: English Language; technology; Web 2.0; teacher; student; learning